Gait evaluation: a tool to monitor bone healing? - Seebeck, P; Thompson, M; Parwani, A; Taylor, W; Schell, H; Duda, G (2005)
BACKGROUND: Current clinical methods for monitoring fracture healing are often invasive and inaccurate. This paper evaluates the use of a pressure sensitive platform to improve monitoring. METHODS: Standardised 3 mm diaphyseal bone defects were created in the right tibia of 64 female sheep and stabilised with either a rigid monolateral external fixator or a more flexible variant. Over a nine week healing period gait parameters were measured using a pressure sensitive platform and interfragmentary movements at the fracture site were monitored. Frequency spectra were calculated for the ground reaction forces. The tibiae were tested biomechanically after sacrifice and callus sections were analysed histomorphometrically. FINDINGS: All animals unloaded the operated and overloaded the contralateral hindlimb. Callus mineralisation and stiffness, as well as limb loading increased during healing whilst interfragmentary movements were reduced. Larger interfragmentary movements resulted in a slower fracture healing rate as documented histologically and biomechanically. Frequency analysis showed upto 14 dB loss of power at frequencies associated with bone mechanotransduction at four weeks postoperatively, reducing to a 3 dB loss at nine weeks. INTERPRETATION: Gait analysis is a valuable tool for monitoring the course of fracture healing. Different fixation stiffnesses caused different initial interfragmentary movements leading to different healing rates. Ground reaction forces were strongly related to the course of callus mineralisation and thus directly reflected the recovery of stiffness at the fracture site. Reduced levels of loading frequencies that may affect bone healing persist to nine weeks postoperatively.